PEMBELAJARAN KITAB SALAF DENGAN METODE DISKUSI DI PESANTREN KHATAMUN NABIYYIN JAKARTA - Siskandar Siskandar; Firman Ma’duali (el-Moona: Jurnal Ilmu Pendidikan Islam, 2019)
The results found in this study are: First, the discussion method is conducted in the form of questions and answers between teachers and students when teaching the bandongan model. This discussion method is used in the deepening of learning, especially in the books of the Salaf. Santri is formed in two groups which are pros and cons to a problem. In this discussion each group discusses with various academics literature. This discussion is sometimes made in the Santri Study Club (SSC) model which follows the Indonesia Lawers Club (ILC) model. Besides the discussion method is also used in the form of presentations, each student is assigned to present a discussion theme in a book of salaf then discuss together the purpose of the contents of the book. Likewise in the daily discussion called Mubahatsah each santri was formed into several small groups. Each of these groups discussed the material obtained from the teachers in class in turn. Second, the discussion model in the pesantren khatamun nabiyyin is different from the discussion model in the teaching and learning process in general. If the discussion is generally carried out freely with free conclusions as well, then the discussion at the Khatamun Nabiyyin pesantren is conducted in a guided manner to explore a particular discussion, with conclusions that are free but still in accordance with the knowledge taught by the kyai or cleric.